Meningkatkan Kesadaran Masyarakat Mengenai Kerelawanan Tanggap Bencana Dan Protokol Kesehatan Dimasa Pandemi - Siti Hamidah; Sri Hidayah; Cindy Yuliastara; Muhammadi Dimas Yanuar; Yustikarina; Agustiani; Nur Jannah; Hatmawati; Sellawati (Journal of Empowerment and Community Service (JECSR), 2021)
The flood disaster that hit Kabupaten Banjar in early 2021 maded these area got disaster alert status. The flood disaster struck and also coincided with the Covid-19 pandemic disaster made people affected by floods aware of the importance of disaster mitigation and also the importance of a village being prepared to face possible disasters. KKN-Tematik Fisip ULM which carries the theme "Village Tourism and Disasters Resilient Village" aims to develop villages according to the potential and problems they need to face. From this KKN-Tematik Fisip activities, it is hoped that it can build the village into a disaster-resilient village or village tourism. The socialization of disaster volunteerism in Sungkai Baru village is hoped that the community will understand the mechanism of volunteerism by cooperating with the Banjar Regency BPBD as a speaker.